Endovascular treatment beyond 24 hours from the onset of acute ischemic stroke: the Italian Registry of Endovascular Thrombectomy in Acute Stroke (IRETAS). (3rd November 2021) - Casetta, Ilaria; Fainardi, Enrico; Pracucci, Giovanni; Saia, Valentina; Vallone, Stefano; Zini, Andrea; Bergui, Mauro; Cerrato, Paolo; Nappini, Sergio; Nencini, Patrizia; Gasparotti, Roberto; Saletti, Andrea; et al.
Abstract : Background: Clinical trials and observational studies have demonstrated the benefit of thrombectomy up to 16 or 24 hours after the patient was last known to be well. This study aimed to evaluate the outcome of stroke patients treated beyond 24 hours from onset. Methods: We analyzed the outcome of 34 stroke patients (mean age 70.7±12.3 years; median National Institutes of Health Stroke Scale (NIHSS) score 13) treated with endovascular thrombectomy beyond 24 hours from onset who were recruited in the Italian Registry of Endovascular Thrombectomy in Acute Stroke. Selection criteria for patients were: pre-stroke modified Rankin scale (mRS) score of ≤2, non-contrast CT Alberta Stroke Program Early CT score of ≥6, good collaterals on single phase CT angiography (CTA) or multiphase CTA, and CT perfusion mismatch with an infarct core size ≤50% of the total hypoperfusion extent or involving less than one-third of the extent of the middle cerebral artery territory evaluated by visual inspection. The primary outcome measure was functional independence assessed by the mRS at 90 days after onset. Safety outcomes were 90 day mortality and the occurrence of symptomatic intracranial hemorrhage (sICH). Results: Successful recanalization (Thrombolysis in Cerebral Infarction score of 2b or 3) was present in 76.5% of patients. Three month functional independence (mRS score 0–2) was observed in 41.1% of patients. The case fatality rate was 26.5%. and the incidence of sICH was 8.8%. Conclusions: These findings suggest that, in a real world setting, very late endovascular therapy is feasible in appropriately selected patients.